2006
DOI: 10.1021/es061076j
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity in Situ Monitoring of NO3 in an Atmospheric Simulation Chamber Using Incoherent Broadband Cavity-Enhanced Absorption Spectroscopy

Abstract: We describe the application of incoherent broadband cavity-enhanced absorption spectroscopy (IBBCEAS) for the in situ detection of atmospheric trace gases and radicals (NO3, NO2, O3, H2O) in an atmospheric simulation chamber under realistic atmospheric conditions. The length of the optical cavity across the reaction chamber is 4.5 m, which is significantly longer than in previous studies that use high finesse optical cavities to achieve high absorption sensitivity. Using a straightforward spectrometer configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
127
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 51 publications
0
127
0
1
Order By: Relevance
“…The sensitivity obtained in these experiments is amongst the highest reported, when compared to other BB-CEAS studies. Venables et al [4] report the highest sensitivity of 5 × 10 -10 cm -1 , in an incoherent BB-CEAS study (over a 60 s acquisition time) for the detection of NO 3 around 660 nm. This is ~ 10 times better than the sensitivity reported here, but this has been achieved using an optical cavity of physical length 4.5 m (some 18 times longer than that used in this study).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The sensitivity obtained in these experiments is amongst the highest reported, when compared to other BB-CEAS studies. Venables et al [4] report the highest sensitivity of 5 × 10 -10 cm -1 , in an incoherent BB-CEAS study (over a 60 s acquisition time) for the detection of NO 3 around 660 nm. This is ~ 10 times better than the sensitivity reported here, but this has been achieved using an optical cavity of physical length 4.5 m (some 18 times longer than that used in this study).…”
Section: Resultsmentioning
confidence: 98%
“…The resolution that has been chosen here reflects the 'shape' of the spectral signatures of the target species such as acetone and isoprene that on the whole are featureless on the 1 cm -1 scale. Increasing the resolution beyond this will lead to a reduction in signal/noise (the S/N ratio) for these species for measurements taken over equivalent acquisition times, but may well lead to a slight increase in S/N for the narrow band absorbers such as CO 2 , CH 4 and H 2 O. It is worth noting that, at least in terms of resolution, any such experiment of this sort can be optimally configured depending upon the target species.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work with broadband cavity systems has largely been applied to trace gas analysis, in which the reflectivity of the dielectric mirrors is usually maximized to increase the sensitivity of the system to small absorptions. [17][18][19][20][21][22][23][24] Prior studies have used bandwidths of 20 to 80 nm because increasing the reflectivity tends to narrow the high reflectivity region of the mirrors. 17,19 For measuring absorption cross-sections, on the other hand, it would be preferable to have a bandwidth sufficiently broad to cover the absorption band of the compound of interest.…”
Section: Introductionmentioning
confidence: 99%
“…those techniques that utilise broad-band emission sources, are increasing in popularity where it is desirable either to measure several compounds simultaneously that absorb in different spectral regions or where specificity is required for target species with extended absorption features (such as relatively large molecules or surface/liquid-borne species). Several studies have been reported that combine different broad-band sources such as arc-lamps [1][2][3][4][5][6] and light emitting diodes (LEDs) [7][8][9][10][11][12] with dispersive and interferometric detection schemes to detect gas phase species such as iodine oxides, 5 NO x compounds, 7,8,10,11 and solutions containing dyes (e.g. coumarin 334, brilliant blue-R, and rhodamine B and 6G) 9,12,13 which absorb at visible wavelengths.…”
Section: Introductionmentioning
confidence: 99%